Post a New Question


posted by on .

prove that
_______1______ - ___1___ =__1___
sec x-tan x cos x cos x
- _______1______
sec x + tan x

  • maths - ,

    I will rewrite the question as:

    1/(sec(x)-tan(x)) - 1/cos(x) = 1/(cos(x) - 1/(sec(x)+tan(x))

    transpose terms to get:
    1/(sec(x)-tan(x)) + 1/(sec(x)+tan(x)) = 2/cos(x)

    Add the two fractions on the left and simplify using sec2(x)=1+tan2(x) on the left-hand side to get 2sec(x)=2/cos(x).

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question